PENGARUH KEPERCAYAAN DIRI TERHADAP KEMAMPUAN PUBLIC SPEAKING PADA PESERTA DIDIK DI YAYASAN ISLAM MIFTAHUS SHIBYAN KEDIRI - Hasanah, Uswatun; Ma`na, Ali (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 2024)
Self-confidence is a person's belief in all aspects of their strengths and this belief in feeling capable of achieving various goals in their life. This research aims to determine: (1) The level of self-confidence of students at the Miftahus Shibyan Islamic Foundation (2) Public speaking abilities; (3) how does self-confidence influence the public abilities of Miftahus Shibyan Plosoklaten Kediri Islamic Foundation students. This research is ex post facto research using a quantitative data approach. The subjects in this research were students of the Miftahus Shibyan Islamic Foundation in the teenage age category. Data collection methods use questionnaires and documentation. Test the validity of the instrument using Product Moment correlation and test reliability using Cronbach's Alpha. Data analysis uses descriptive analysis; analysis prerequisite tests consisting of normality tests, linearity tests, and regression analysis. The results of the research show that: (1) The level of self-confidence of students at this foundation is relatively low, namely 44.36%, (2) The level of self-confidence of students at this foundation is also relatively low, namely 45.7%, (3) there is a significant influence self-confidence in public speaking skills was 82.8% with ??1? = 0.910; ?2x1y = 0.828. From the results of the objectives above, we can understand that high public speaking abilities depend on the student's level of self-confidence. Students who tend to have a high level of self-confidence can indirectly make these individuals brave enough to appear in public so that they can improve their public speaking skills.